2014
DOI: 10.12681/mms.606
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the ecological status of Mediterranean coastal lagoons using macroinvertebrates. Comparison of the most commonly used methods

Abstract: Benthic communities were studied twice (during the autumn and spring) in three Mediterranean coastal lagoons located in Greece (Logarou) and Italy (Cesine and Grado-Marano). The species composition and distribution, community diversity, species richness, dominant taxa and their ecological identity, benthic trophic and biomass size structure were investigated in these lagoons and the results were correlated with the environmental variables. The overall similarity based on species composition and abundance among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Identifying macrobenthos morphologically to the species level was conducted by using standard macrobenthos identification books (Fauchald 1977;Dharma 2005) and nomenclature writing following World Register of Marine Species (WoRMS: http://www.marinespecies.org/index.php). Organic carbon and sediment particle size (sand, mud, and clay) were analyzed using the "wet sieving" method (Reizopoulou et al 2014). Water temperature measurements using standard thermometer and brightness are measured with a Secchi disk.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Identifying macrobenthos morphologically to the species level was conducted by using standard macrobenthos identification books (Fauchald 1977;Dharma 2005) and nomenclature writing following World Register of Marine Species (WoRMS: http://www.marinespecies.org/index.php). Organic carbon and sediment particle size (sand, mud, and clay) were analyzed using the "wet sieving" method (Reizopoulou et al 2014). Water temperature measurements using standard thermometer and brightness are measured with a Secchi disk.…”
Section: Methodsmentioning
confidence: 99%
“…The water sample was filtered using a Millipore strainer to analyze the nitrates, nitrites, soluble phosphates with the aid of the spectrophotometer. While water used to measure biological oxygen demand (BOD5) was inputted into dark glass bottles and analyzed by a modification of the Winkler method (Lizarralde and Pittaluga 2010;Reizopoulou et al 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BOPA/BO2A was among the five most used indices in a review of 35 benthic quality assessment indices employed in different countries to assess the impact of 15 different human pressures (Borja et al, 2015). Moreover, in most of these studies, BOPA and BO2A were compared with other indices, mainly BENTIX, AMBI and M-AMBI (see also Boon et al, 2011;Culhane, 2012;Nebra et al, 2014;Reizopoulou et al, 2014). It appeared that, in most cases, the BOPA and BO2A indices tended to overestimate the Ecological Status of the stations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It appeared that, in most cases, the BOPA and BO2A indices tended to overestimate the Ecological Status of the stations (e.g. Caglar and Albayrak, 2012;Reizopoulou et al, 2014;Aguado-Giménez et al, 2015), but the comparisons showed in most of the cited studies did not take into account the revised thresholds proposed by de-la-Ossa-Carretero and , including recent publications (Nebra et al, 2014;Aguado-Giménez et al, 2015). In addition, Keeley et al (2012) pointed out that the Ecological Status classification was underestimated by BOPA when the species richness and abundances of macro-invertebrates were very low, though the use of BOPA was not recommended for abundance <20 ind.…”
Section: Discussionmentioning
confidence: 99%